Analisis Peningkatan Efisiensi Pengelolaan Dana Zakat Melalui Optimalisasi SIMBA di BAZNAS Provinsi Jawa Timur - Risqi, Moh.; Nasrulloh, Nasrulloh (Universitas Islam Negeri Alauddin Makassar, 2024)
This research aims to determine how to increase the efficiency of zakat fund management by optimising SIMBA at BAZNAS East Java Province. This research uses a qualitative descriptive approach method. Where this research can provide an overview of the phenomenon being studied. The research results show that four functions can increase the efficiency of managing zakat funds through optimising SIMBA, including: (1) Planning: Careful planning is required in using the SIMBA application, of course, at BAZNAS East Java Province. (2) Organizing: Regarding arrangements related to determining human resources. Two employees actively and cohesively manage SiMBA operators at BAZNAS East Java Province. (3) Direction: In the briefing process, of course, BAZNAS East Java Province needs the help of a delegation of people with IT expertise from Central BAZNAS to provide a kind of socialisation or technical guidance regarding correct SIMBA governance. (4) Supervision: SIMBA supervision at BAZNAS East Java Province could be further improved, including regular or routine monitoring and evaluation carried out by BAZNAS leadership to compare previous performance and improve future performance.